2015
DOI: 10.3389/fpls.2015.00635
|View full text |Cite
|
Sign up to set email alerts
|

The role of chromatin modifications in somatic embryogenesis in plants

Abstract: Somatic embryogenesis (SE) is a powerful tool for plant genetic improvement when used in combination with traditional agricultural techniques, and it is also an important technique to understand the different processes that occur during the development of plant embryogenesis. SE onset depends on a complex network of interactions among plant growth regulators, mainly auxins and cytokinins, during the proembryogenic early stages, and ethylene and gibberellic and abscisic acids later in the development of the som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 140 publications
2
62
0
Order By: Relevance
“…Different studies show that epigenetic changes might be related to totipotency acquisition, cellular reprogramming, induction of SE, and embryo development [2] [15] [61]. In this work, we observed that both clonal lines showed different genetic and epigenetic patterns before beginning the induction process (even when using the same explant).…”
Section: Dynamics Of Dna Methylation Patterns During Se Inductionsupporting
confidence: 52%
“…Different studies show that epigenetic changes might be related to totipotency acquisition, cellular reprogramming, induction of SE, and embryo development [2] [15] [61]. In this work, we observed that both clonal lines showed different genetic and epigenetic patterns before beginning the induction process (even when using the same explant).…”
Section: Dynamics Of Dna Methylation Patterns During Se Inductionsupporting
confidence: 52%
“…These data indicate that histone deacetylation is a conserved mechanism in plants to repress embryo identity outside the seed. Similar to H3K27me3, levels of histone acetylation and the activity of HDACs has also been found to change after hormone‐induced indirect SE (De‐la‐Peña, Nic‐Can, Galaz‐Ávalos, Avilez‐Montalvo, & Loyola‐Vargas, 2015; Lee, Park, Jung, & Seo, 2016), providing indirect evidence that histone deacetylation may also play a role in the reprogramming of cells in the early stages of indirect SE.…”
Section: The Role Of Chromatin Modifications In Somatic Embryogenesismentioning
confidence: 87%
“…The extent to which chromatin reprogramming is required prior to SE probably depends on the explant and culture system in which SE is induced, and might also require additional chromatin modifications such as changes in DNA methylation, which are often associated with SE (De‐la‐Peña et al., 2015). Direct SE appears to involve less reprogramming than indirect SE and probably occurs in cells where totipotency genes are transcriptionally accessible.…”
Section: The Role Of Chromatin Modifications In Somatic Embryogenesismentioning
confidence: 99%
“…8). There is an epigenetic reprogramming during the SE and the presence of somaclonal variation among the regenerated plants ( De-la-Peña et al 2015;Mahdavi-Darvari et al 2015;Nic-Can et al 2015;Solís et al 2015). This variation can be the result of chromosomal aberrations, genetic alterations, epigenetic regulations, and transposable elements.…”
Section: Somatic Embryogenesismentioning
confidence: 99%